From the Big Bang to the Nucleosynthesis - Bracco, A. (IOS Press, 2014)
Physicists have devoted much effort to reproducing the conditions of the primordial universe in laboratory conditions in their quest to work out a comprehensive theory of the appearance and evolution of nuclear matter. Whether it be trying to recreate the predicted primordial state of high-energy density matter in which quarks and gluons are effectively deconfined - the so-called Quark Gluon Plasma (QGP) - or exploring the structure and reaction properties of very unstable nuclei in experiments using radioactive beams, they have striven to understand the events which characterized the Big Bang and the various nucleosynthesis mechanisms which occur in the stars. This book contains the proceedings of the 2010 Enrico Fermi summer school held in Varenna, Italy, in July 2010, and devoted to the present understanding of the primordial universe and the origin of the elements, as achieved by studying nuclei and their constituents in extreme regimes of energy and composition. Subjects covered include: QGP formation; exotic nuclei, their degrees of freedom from the ground state and the properties of the excited states; the complex, but appealing theory describing the supernovae explosion and neutron stars; dark energy and matter; Big Bang nucleosynthesis and energy and solar neutrino production; nuclear cosmochronology; beta and gamma decay relevant for the nucleosynthesis of heavy nuclei. The annual Enrico Fermi summer school is internationally renowned and this book will be of great interest to all those involved in the field of nuclear physics.